2009
DOI: 10.1021/cm9006266
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Encapsulated Metal Oxide Hollow Nanoparticles and Metal Oxide Hollow Nanoparticles: A General Synthesis Strategy and Its Application to Lithium-Ion Batteries

Abstract: A novel and general strategy for the synthesis of carbon-encapsulated metal oxide hollow nanoparticles (HNPs) and pure metal oxide HNPs was developed from carbon-encapsulated metal nanoparticles by controlled oxidation in the air. The materials were characterized by transmission electron microscopy, scanning electron microscopy, and X-ray diffraction measurements. It was found that the morphologies and compositions of HNPs were easily tailored through adjustment of the oxidation conditions. When used as the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(86 citation statements)
references
References 67 publications
3
83
0
Order By: Relevance
“…Transition metal oxide NPs have many applications as catalyst [1][2][3][4][5] , sensors [6][7][8][9] , superconductors [10][11] and adsorbents [12][13] . Metaloxides constitute an important class of materials that are involved in environmental science, electrochemistry, biology, chemical sensors, magnetism and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxide NPs have many applications as catalyst [1][2][3][4][5] , sensors [6][7][8][9] , superconductors [10][11] and adsorbents [12][13] . Metaloxides constitute an important class of materials that are involved in environmental science, electrochemistry, biology, chemical sensors, magnetism and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…The XRD pattern of hollow spheres of calcinated NPs is shown in Figure 5(a) that indicates the high crystalline form of iron oxide NPs due to the iron precursor used and also due to calcination (to remove the carbon core at high temperature). Before calcinations no crystalline peaks were observed indicating the amorphous structure [9]. XRD peaks can be well indexed to -Fe 2 O 3 crystals and rhombohedral phase with JCPDS card number 33-0664.…”
Section: Resultsmentioning
confidence: 97%
“…Among them, template methods are the most effective way to produce hollow structures and are used typically for the synthesis of core shell structure leading to the coating of desired materials on the templates followed by the removal of templates. Hard and soft templates of different types are being used for instance carbon, acting as hard templates while emulsions, gas bubble, vesicles, and micelles were performing the soft template materials [9]. Template methods are most effective in the formation of hollow structures in accordance with the uniformity [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[68] In 2009, Song et al reported a Kirkendall-effect-assisted strategy for the fabrication of α-Fe2O3 (Figures 3a and 3b) and carbon encapsulated α-Fe2O3 (α-Fe2O3@C) hollow nanoparticles. [69] The synthesis generally involved two steps, the preparation of Fe3C@C nanoparticles via co-carbonization and the controlled oxidation of Fe3C@C nanoparticles. During the controlled oxidation, Fe3C@C was converted into either α-Fe2O3@C (280 °C for 5 h) or pure α-Fe2O3 hollow nanoparticles (280 °C for 24 h) through nanoscale Kirkendall effect.…”
Section: Introductionmentioning
confidence: 99%